Experimental characterization of the hygrothermal ageing effects on the bulk mechanical properties and lap-shear strength of the novel bio-based epichlorohydrin/cardanol adhesive. Issue 1 (2nd January 2022) - Tzatzadakis, Vasileios; Tserpes, Konstantinos
ABSTRACT: In the present paper, the effects of hygrothermal ageing on the bulk mechanical properties and lap-shear strength of the novel bio-based epichlorohydrin/cardanol adhesive have been studied by tension tests, fracture toughness tests and single-lap shear tests on bonded CFRP and aluminum specimens. The thermomechanical properties of the adhesive have been characterized using dynamic mechanical analysis tests. Ageing of the specimens has been realized inside an environmental chamber under the conditions of 70°C/85%RH until saturation. The glass transition temperature of the adhesive is reduced by 13.8%. The results from the tension tests reveal that ageing has caused a reduction of Young's modulus by 13.4% and of tensile strength by 34.9%. Fracture toughness is reduced by 3.2% while the plasticity caused by the ageing has led to a less brittle behavior. Contrary to the bulk mechanical properties, the lap-shear strength of both the CFRP and aluminum joints is not affected. These findings reveal that although Tg and tensile properties of the bio-adhesive are significantly reduced by the ageing, the fracture toughness and lap-shear strength, which largely determine the adhesion capacity of the adhesive, are not affected.